Kajian Terhadap Tahap Kepuasan Bekerja Pegawai-Pegawai Professional dan Sokongan di Ibu Pejabat, Jalan Sultan Salahuddin, Kuala Lumpur - Saliha, Che Daud (2004)

(untitled)
This study was conducted to measure the level of job satisfaction and identifying factors that influence job satisfaction professionals and supporting staff in JKR Headquarters which was located at Jalan Sultan Salahuddin, Kuala Lumpur. Various factors and variables were tested to identify to identify the significant correlation and factors and variables were tested to identify the Significant correlation and factors influencing job satisfaction such as demography, work environment, leadership and organization commitment. Elements in each variables were developed based on theories, literatures and opinion of Maslow (1970), Taylor (1966), Alderfer (1972), Hertzberg (1959), Weaver (1980), Cranny (1992), Mohd Majid (1990), Stephen (1996), Locke (1976) and Owen (2000). The instruments used in the study was a set of questionnaires. About 250 set of questionnaires were distributed where 162 questionnaires were returned which is about 81 % responded. The data obtained were analysed by using SPSS software. As an overall, the level of job satisfaction in JKPL Headquarters recorded average scores. The variables were tested to identify the means and correlation. The output of test conducted were two factors, which showed strong positive relationship and great influence to job satisfaction, namely working environment and leadership. The findings of the study would be a feedback to the organization to improve the job satisfaction level and to review its role and tasks so that it could be implemented efficiently and effectively.